Economic and Political Determinants of the Effects of FDI on Growth in Transition and Developing Countries. (2nd February 2016) - Elkomy, Shimaa; Ingham, Hilary; Read, Robert
Abstract: This study investigates the role of human capital and political development in determining the magnitude of the effects of foreign direct investment (FDI) on growth for a panel of 61 transition and developing countries for the period 1989 to 2013. A baseline growth model incorporating these variables is tested and then extended to include FDI interaction effects with human capital (measured using secondary school enrollment data) and political development (based on Economist Intelligence Unit Democracy Index scores). These growth interaction effects between FDI and human capital vary according to regime type. Political development in conjunction with FDI appears to suppress the effects of FDI on growth in authoritarian countries while enhancing them in hybrid democracies. For more democratic countries, domestic investment is a more important driver of growth. The effects of FDI on growth in the ten transition economies included in the sample data set are found to be insignificant. Although this result might seem to differ from a priori expectations, it is in line with the findings of most earlier studies that cover the period up to 2004. The paper also provides no strong evidence that a critical threshold of human capital is required to generate beneficial spillover growth effects from inflows of FDI. The paper provides new and more detailed insights into the effects of FDI on growth with particular respect to human capital and political regime covering a large number of transition and developing countries based on an up‐to‐date data set covering a 25‐year period to 2013. © 2016 Wiley Periodicals, Inc .